The measurement of zombie enterprise under information asymmetry–a case of China’s iron and steel industry - Shiue-Hung Lin (Journal of Applied Economics, 2023)
ABSTRACTThe problem of zombie enterprises originated in Japan’s bubble economy around 1990. Afterward, after China’s oversupply problem in 2016, it gained attention and received policy support from the Chinese government in solving related problems. The contribution of this measurement is to integrate the investor’s demand index for listed companies and the company’s actual production and operation performance simultaneously. Based on the panel data of 28 Chinese-listed iron and steel enterprises from 2003 to 2022, the simulation and empirical analysis are carried out. Our research found that the 28 listed steel enterprises in China generally performed poorly from 2007 to 2016, and even some steel enterprises had negative operating profits, but they still survived in the market. In addition, there is a problem of information asymmetry between the actual operation of the enterprise and the capital or financial market in the listed steel industry in China.